Documenting Single-Generation Range Shifts of Periodical Cicada Brood VI (Hemiptera: Cicadidae: Magicicada spp.). (13th April 2021) - Cooley, John R; Marshall, David C; Simon, Chris
Abstract: Historically, most North American periodical cicada (Hemiptera: Cicadidae: Magicicada spp. Davis 1925) distribution records have been mapped at county-level resolution. In recent decades, Magicicada brood distributions and especially edges have been mapped at a higher resolution, aided by the use of GIS technology after 2000. Brood VI of the 17-yr cicadas emerged in 2000 and 2017 and is the first for which detailed mapping has been completed in consecutive generations. Overlaying the records from the two generations suggests that in some places, Brood VI expanded its range slightly between 2000 and 2017, although the measured changes are close to the lower limit of detectability given the methods used. Even so, no simple alternative to range expansion easily accounts for these observations. We also bolster Alexander and Moore's assertion that M. cassini does not occur in Brood VI.